A Rare Instance of Pterygopalatine Fossa Tumor With Hearing Loss as the Main Complaint. Issue 2 (11th March 2023) - Liu, Yue; Zhao, Xue; Yu, Dan
Abstract : Pterygopalatine schwannomas are rare tumors which usually cause the symptoms of the traffic area by the tumors in the pterygopalatine fossa which is difficult to resection. This paper presents 1 rare case of pterygopalatine fossa tumor with hearing loss as the main complaint treated by total resection through the endoscopic endonasal approach.